Pengaruh Kadar Immunoglobulin Gamma (lgG) Kolostrum Induk Terhadap IgG Serum Darah Anak Pada Sapi Friesian Holstein - Syarifuddin Hidayat, ,- (2009)
Neonatal calves are born agammag/obulinemic or hypoglohulinemic and must obtain immunoglobulin (lg), primarily gamma immunoglobulin (lgG) during the period of macromoleculer transport within the first 24 hour of life. The aim of this study is to evaluate the effect of colostral IgG concentration of Friesian Holstein cow consumed by calf soon after birth, on determining blood serum IgG concentration of calf. As much 30 colostrum samples (each of 1-2 ml) from 30 cows and 30 blood serum samples (each of 1-2 ml) from 30 calves were collected from several dairy fanners in sub-district Tutur, District Pasuruan - East Java Province. The colostrum samples were measured first in location by using colostrometer to estimate lgG concentration. The measurement of both colostral and blood serum IgG concentration were confirmed by Direct Enzyme-linked Immunosorbent Assay (Direct-ELISA) technique. Datas were utilized by regression analyses using SPSS for windows 12.00. The result showed that concentration ofcolostral IgG consumed by calf had significant effect (P<0,05) on concentration of calf blood serum lgG. Therefore colostral IgG concentration can be used as predictor (R2 = 0, 180) on blood serum IgG concentration of calf.